Identification of devious behavior bullying in physical education with the implementation of group tournaments in elementary school - Akbar, Muhammad Army; Rahmadi, Rahmadi; Warni, Herita (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2024)
This research aims to identify the frequency and types of bullying behavior in physical education learning in elementary schools. The main focus is understanding the prevalence and types of bullying behavior (physical, verbal, social, and cyberbullying) and their impact on students in the physical education context. This research uses a survey method with an observational design by implementing part of the TGT learning model, namely group tournaments for its implementation. The research population was grade 4 students at elementary schools in Karang Mekar District, Banjarmasin City. The sample was selected by purposive sampling. The main instrument is an observation sheet that includes the frequency of bullying incidents and types of bullying behavior. Data was collected by two independent observers filling in observation sheets and analyzed using descriptive statistical techniques with SPSS. The results indicate that in Sample 1, the highest average bullying behaviors were teasing (1.18) and cynical stares (1.05). In Sample 2, teasing also recorded the highest average (1.33), followed by pushing (0.93). Meanwhile, in Sample 3, the average occurrences were lower, with teasing having the highest average (0.48). Overall, the frequency of bullying behavior varied across schools, with teasing and cynical stares being the most common behaviors. This research reveals that bullying behavior in physical education learning varies depending on the school and the indicators studied. Results demonstrate the importance of effectively monitoring and managing bullying behavior to create a safe and inclusive learning environment.